Perspectives of EFL teacher trainers and pre-service teachers on continued mandatory distance education during the pandemic - ÇAMLIBEL ACAR, ZEYNEP CUMHUR (Elsevier Ltd, 2022)
Due to the Covid-19 pandemic, the world experienced a fast transition to online education, starting in March 2020. This study aimed to review the process from the perspectives of prospective teachers and teacher trainers in a foreign language teacher education program after two semesters of mandatory distance education to make adjustments and take precautions for online possibilities in the future. Data was collected through questionnaires composed of open- and closed-ended items. A range of themes emerged from the responses, presented in terms of participants’ preferences, their perceived benefits and challenges and recommendations for the future. © 2022 Elsevier Ltd
Keywords: Covid-19; Distance education; EFL; Pre-service teachers; Teacher education; Teacher trainers